Reducing Stress and Heart Rate by Meditation and Breathing Relaxation among the Female Students in the Faculty of Medicine at Mutah University - Aldahadha, Basim Mohammad; Al-Domour, Noor Mahmoud (Dirasat: Educational Sciences, 2020)
This study aims at identifying the effectiveness of two group-counseling programs for meditation and breathing relaxation on reducing stress and heart rate among the female students in the faculty of Medicine at Mutah University. The sample consisted of 45 students. They were divided into three groups; the first experimental group that were trained on meditation, the second group that were trained on breathing relaxation and a control group. The stress scale and the heat rate scales were applied. The results of the study showed that there are differences between the experimental groups and the control group in favour of experimental groups on the means of heart rate and stress at the post testing. Furthermore, the results showed that the individuals in the groups that were trained using the meditation and breathing relaxation programs retained the impact of the programs on the scale of the stress and the heart rate despite the passing of a month from the termination of the two programs. Finally, results show that there were significant differences in the heart rate due to the meditation program, while there were no differences between the two programs on the stress scale. The study recommended conducting more research on the effectiveness of meditation and breathing relaxation on patient samples.